2017
DOI: 10.1016/j.ijpddr.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between tafenoquine and artemisinin-combination therapy partner drug in asexual and sexual stage Plasmodium falciparum

Abstract: The 8-aminoquinoline tafenoquine (TFQ), a primaquine derivative, is currently in late-stage clinical development for the radical cure of P. vivax. Here drug interactions between TFQ and chloroquine and six artemisinin-combination therapy (ACT) partner drugs in P. falciparum asexual stages and gametocytes were investigated. TFQ was mostly synergistic with the ACT-partner drugs in asexual parasites regardless of genetic backgrounds. However, at fixed ratios of 1:3, 1:1 and 3:1, TFQ only interacted synergisticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 49 publications
1
10
1
Order By: Relevance
“…The combination of PND with PG seemed to provide more synergistic effect than with ATQ, or TQ. Our results on TQ-PND combination were different from the previous report demonstrating TQ had synergistic interaction with PND [56]. The discrepancy may be accounted for by the drug concentration used to test the drug interactions.…”
Section: Discussioncontrasting
confidence: 99%
“…The combination of PND with PG seemed to provide more synergistic effect than with ATQ, or TQ. Our results on TQ-PND combination were different from the previous report demonstrating TQ had synergistic interaction with PND [56]. The discrepancy may be accounted for by the drug concentration used to test the drug interactions.…”
Section: Discussioncontrasting
confidence: 99%
“…Other drugs, such as artemisinin and atovaquone, are known to be effective only against early gametocyte stages (54-56). Only a few compounds have shown effects against mature gametocytes in vivo in humans, including methylene blue (57), the 8-aminoquinoline primaquine (58), and tafenoquine (16). The mode of action of primaquine in gametocytes is unclear, but it has been suggested that it targets mitochondrial function (59).…”
Section: Discussionmentioning
confidence: 99%
“…ACTs appeared as a solution for drug-resistant P. falciparum malaria, with rapid elimination of asexual parasites and young gametocytes (14,15). However, ACTs are ineffective against mature gametocytes, allowing persistent parasite transmission after treatment (16). Besides using potent antimalarial drugs against the blood-stage parasites, blocking through vector control or utilizing transmissionblocking drugs is essential for the effective control of malaria transmission.…”
mentioning
confidence: 99%
“…The major advantage of tafenoquine over primaquine is its considerably longer plasma elimination half-life (approximately 15 days) (12,13) which allows for single dose (radical cure) or weekly administration for prophylaxis, thus reducing adherence issues commonly associated with primaquine dosing regimens (14). Although not currently approved for transmission blocking, the potential utility of tafenoquine for such is evident given its gametocytocidal activity in vitro (15) and transmission blocking activity in murine models (16). Like primaquine, tafenoquine can cause severe hemolytic anemia in G6PD-deficient individuals at currently recommended doses (17); however, as with primaquine, it is possible that a sufficient safety margin may be present for its therapeutic use in G6PD-deficient individuals (18).…”
Section: Introductionmentioning
confidence: 99%
“…Tafenoquine is a long acting analogue of primaquine that has been recently approved for malaria prophylaxis and for radical cure of P. vivax malaria (11). The major advantage of tafenoquine over primaquine is its considerably longer plasma elimination half-life (approximately 15 days) (12, 13) which allows for single dose (radical cure) or weekly administration for prophylaxis, thus reducing adherence issues commonly associated with primaquine dosing regimens (14). Although not currently approved for transmission blocking, the potential utility of tafenoquine for such is evident given its gametocytocidal activity in vitro (15) and transmission blocking activity in murine models (16).…”
Section: Introductionmentioning
confidence: 99%